DEVELOPMENT STRATEGIES FOR CATTLE CORPORATION VILLAGES IN ACEH BESAR REGENCY - Firdaus; Zakiah; Sofyan (CV. Radja Publika, 2024)
The local government has made several efforts to increase the population using technology, but so far the availability of existing resources has not been optimized. This is realized by the ability to raise beef cattle, which is still mostly done as a side activity with a very simple and distributed maintenance system. To be able to anticipate the problems that arise, a measurable and directed concept is needed to establish a strategy for developing beef cattle businesses in Aceh Besar Regency through the Cattle Corporation Village. The objectives of the study were (1) to identify the internal and external conditions that support the development of Cattle Corporation Village in Aceh Besar Regency; (2) to formulate strategies to develop cattle production through the development of Cattle Corporation Village in Aceh Besar Regency. The methods used in this research are descriptive method (SWOT) and quantitative method (QSPM). Based on the results, the results of the IFE matrix analysis show a strong internal position. The main strengths in this cattle corporation village are Availability: (1) potential land; (2) feed; and (3) sufficient water sources. Meanwhile, the main internal weakness in the cattle corporation village is the inadequate marketing system. The results of the EFE matrix analysis show a strong external position. The main opportunity in the cattle corporation village is the availability of feed raw materials and agricultural waste that is abundant and has not been maximally utilized. The main threat to the village corporation village is the decline in agricultural production. The results of the IFE and EFE matrix analysis show that the IFE matrix total weight score of 3.52 is in a high position and the EFE matrix total weight score of 3.40 is in a strong position. This indicates that Cattle Corporation Village is in cell I, which can be described as growing and developing. Based on the SWOT Matrix, 11 (eleven) alternative strategies can be obtained, then grouped into 6 (six) strategies that will be tested using QSPM Analysis. Based on the QSPM results, the priority order of the Cattle Corporation Village Development strategy is obtained, namely: Optimizing livestock businesses in the farming system of both food crops and plantations; Increasing the quantity and quality of cattle production; Intensifying the management of reproductive diseases and livestock health; Establishing good cooperation with local governments, educational institutions and the private sector both in the provision of program assistance and the development of Corporate Villages; Managing human resources in terms of managerial and operational efficiency; and Providing market information and coaching for cattle farmers/entrepreneurs/traders.